Remark on the Neves-Wotzasek constraints conversion method - Abreu, Everton M. C. [UNESP]; Ilha, Anderson (American Physical Society (APS), 2000)
In this work we give an alternative way which generalizes the recently implemented Neves-Wotzasek method of conversion from second to first-class systems. We have proved that this generalization is correct reproducing the results given in the literature using the case of a sphere with an antisymmetric generator as an example. ©2000 The American Physical Society.